The Influence of Animated Video Education on Children's Knowledge about Type-1 Diabetes Mellitus in Primary School Negeri 1 Mujur Kroya - Plantica Putri Ady; Atika Dhiah Anggraeni; Fanny Adistie (Proceedings Series on Health & Medical Sciences, 2024)
Background: Type 1 diabetes mellitus (IDDM) is a chronic disease in children with an increasing incidence worldwide. The increase in the prevalence of DM sufferers in all ages in Central Java Province reached 152,075 cases. While there are 65 patients under 15 years old who are recorded to suffer from IDDM. Thus, there needs to be a preventive measure so that children understand more about the prevention and treatment of IDDM, one of which is by educating about type-1 diabetes mellitus through techniques that attract children, one of which is using animated videos. Objective: To determine the effect of animated video education on children's knowledge about IDDM at SD Negeri 1 Mujur Kroya. Method: This study uses the Pre-Experiment method with the design of One Group Pretest-Posttest Design. The sampling technique used is total sampling with a total of 40 research samples. Results: Showing the majority of respondents' characteristics are female, there is a history of DM descent. Knowledge before the category intervention was lacked and after the good category intervention was carried out. The results of the bivariate test showed that the value (p value 0.0001< 0.005) had a significant effect with a value of 0.001 on providing animated video education on children's knowledge about IDDM at SD Negeri 1 Mujur which was statistically tested to increase the average knowledge of children about type-1 diabetes mellitus by 9,464 based on the DKQ-24 questionnaire. Conclusion: Animated video education has an effect in increasing students' knowledge about IDDM.